Study of pragmatic transfer in persuasion strategies by Chinese learners of English - Jiemin Bu, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
This study investigates pragmatic transfer in persuasion strategies by Chinese learners of English. The subjects of the study include ten native English speakers, ten Chinese learners of English and ten native Chinese speakers. All of them are university students. The classification of persuasion strategies is mainly based on Hardin‘s classification of lexical and pragmatic realization of persuading speech act. The data is collected by means of a discourse complete test questionnaire The Chi-square test is used to compare frequencies of use of persuasion strategies by the Chinese learner of English group, the native English group and the native Chinese group. Results indicate that although all three groups use complaint strategy most frequently and opting out strategy least frequently, the Chinese learner of English group displays advice/suggestion/recommendation strategy more frequently than the native English group. The Chinese learner of English group also uses opinion-proving strategy less frequently than the native English group and never uses consolation/ condolence strategy. Such pragmatic transfer is transferred from Chinese culture and Chinese thinking pattern, which provides pedagogical implication for language teachers to develop Chinese students‘ English pragmatic competence